1994
DOI: 10.1007/bf00019502
|View full text |Cite
|
Sign up to set email alerts
|

HMG protein binding to an A/T-rich positive regulatory region of the pea plastocyanin gene promoter

Abstract: Gel retardation assays using pea nuclear extracts have detected specific binding to regions of the promoter of the pea plastocyanin gene (petE). Several complexes which differ in sensitivity to competition with unlabelled promoter fragments and various DNA alternating copolymers, to heat treatment and to digestion with proteinase K have been detected. A protein factor, PCF1, forming one of these complexes was heat-stable and most sensitive to competition with poly(dAdT).poly(dAdT) compared to other alternating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…At least two lines of evidence suggest that the enhancer element increases transcription through the modulation of chromatin structure: (1) the enhancer element fails to increase reporter gene expression when the same constructs are introduced transiently into plant cells, suggesting that the enhancer requires a chromatin context to increase transcription (J.S. Sandhu and J.C. Gray, unpublished data); and (2) the enhancer element interacts strongly with pea HMG-I/Y and HMG-1 proteins (Pwee et al, 1994;Webster et al, 1997), which are "architectural" chromosomal proteins that maintain chromatin in a conformation favorable for transcription (Grosschedl et al, 1994; Grasser, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two lines of evidence suggest that the enhancer element increases transcription through the modulation of chromatin structure: (1) the enhancer element fails to increase reporter gene expression when the same constructs are introduced transiently into plant cells, suggesting that the enhancer requires a chromatin context to increase transcription (J.S. Sandhu and J.C. Gray, unpublished data); and (2) the enhancer element interacts strongly with pea HMG-I/Y and HMG-1 proteins (Pwee et al, 1994;Webster et al, 1997), which are "architectural" chromosomal proteins that maintain chromatin in a conformation favorable for transcription (Grosschedl et al, 1994; Grasser, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…At least two lines of evidence suggest that the enhancer element increases transcription through the modulation of chromatin structure: (1) the enhancer element fails to increase reporter gene expression when the same constructs are introduced transiently into plant cells, suggesting that the enhancer requires a chromatin context to increase transcription (J.S. Sandhu and J.C. Gray, unpublished data); and (2) the enhancer element interacts strongly with pea HMG-I/Y and HMG-1 proteins (Pwee et al, 1994;Webster et al, 1997), which are "architectural" chromosomal proteins that maintain chromatin in a conformation favorable for transcription (Grosschedl et al, 1994; Grasser, 1998).Chromatin structure affects transcription through nucleosomes, the basic structural units of chromatin in eukaryotic cells (Brownell and Allis, 1996;Wolffe and Hayes, 1999). Each nucleosome is composed of two turns of DNA wound around a histone octamer containing two molecules each of H2A, H2B, H3, and H4 and is linked to the next nucleosome by linker DNA.…”
mentioning
confidence: 99%
“…Interestingly, similar short basic repeats have been found in other proteins from bacteria (28), yeast, plants, Drosophila, and mammals. Examples include human HRX (ALL) (18,41), Drosophila HMG D1 (3), chironomous cHMG I (7), pea ATBP-1 (32), rice PF1 (29), and yeast MIF2 and datin (4,44).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the pea PetE enhancer interacts with HMG-I/Y proteins (Pwee et al, 1994;Webster et al, 1997Webster et al, , 2000, which are MAR binding proteins in native chromosomes (Saitoh and Laemmli, 1994). It seems likely that the pea PetE enhancer mediates histone acetylation by first interacting with HMG-I/Y proteins and associating with the nuclear matrix, bringing the minimal promoter in close proximity to the nuclear matrix, which is enriched in protein factors involved in transcription (Razin and Gromova, 1995).…”
Section: The Pea Pete Enhancer Colocalizes With a Marmentioning
confidence: 99%
“…Experimental evidence suggests that the pea PetE enhancer increases transcription by inducing changes in chromatin structure and chromatin accessibility to transcription factors. First, the enhancer interacts with HMG-I/Y and HMG-1 proteins (Pwee et al, 1994;Webster et al, 1997), which are architectural chromosomal proteins that regulate transcription by modulating DNA conformation (Grosschedl et al, 1994;Grasser, 1998). Second, the accessibility of the pea PetE enhancer to nuclease digestion increases when the gene is expressed, suggesting that it adopts a more open chromatin structure for interactions with transcription factors (Chua et al, 2001).…”
Section: Introductionmentioning
confidence: 99%